1996
DOI: 10.1007/bf02506066
|View full text |Cite
|
Sign up to set email alerts
|

Control of the separated flow downstream of a two-dimensional fence by low-frequency forcing

Abstract: Abstract. Streamwise distributions of wall shear-stress, reverse-flow-factor and static pressure were measured in the turbulent separation regions upstream and downstream of a two-dimensional fence. In front of the fence, boundary layer profiles were measured with a pulsed-wire probe traversing out of the wall. The flow was then manipulated by a periodic disturbance which was located upstream of the forward separation region. Two different disturbances were tested: an oscillating spoiler and a two-dimensional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…There is, of course, an extensive literature on these latter instabilities and their control. A comprehensive review is provided by Greenblatt & Wygnanski (2000) and it seems that it is control of these (essentially K-H) instabilities which appears to be the most effective in, inter alia, reducing the size of a separated region (see, for example, Siller & Fernholz 1997). Whether the much lower-frequency modes identified by Hudy et al can be controlled remains an open question.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…There is, of course, an extensive literature on these latter instabilities and their control. A comprehensive review is provided by Greenblatt & Wygnanski (2000) and it seems that it is control of these (essentially K-H) instabilities which appears to be the most effective in, inter alia, reducing the size of a separated region (see, for example, Siller & Fernholz 1997). Whether the much lower-frequency modes identified by Hudy et al can be controlled remains an open question.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…About 5.76 million (400x96x150) grid points were used to mesh the computational domain of size 37Hx6Hx6.75H. In agreement with the results of experiments conducted by Siller and Fernholz (1997) for similar flow conditions, Orellano and Wengle (2000) show that for ReH=10,500 the optimum forcing Strouhal number is related to the low-frequency movement of the entire separation bubble and not to the instability mode of the SSL.…”
Section: Studies Using Les/dns Modelssupporting
confidence: 72%
“…A number of studies have provided more complete information on both time-averaged and instantaneous flow structures, which clearly show the unsteady nature of the flow over surface-mounted obstacles [45][46][47]. Few studies have also considered active flow control by periodic suction/blowing upstream to manipulate the length of the recirculation bubble [48,49]. It was found that the length of the recirculation bubble can be considerably reduced when the forcing frequency is close to the frequency of the shear-layer instability.…”
Section: Introductionmentioning
confidence: 99%